CO2 conversion in a gliding arc plasma: 1D cylindrical discharge model. (18th October 2016) - Wang, Weizong; Berthelot, Antonin; Kolev, Stanimir; Tu, Xin; Bogaerts, Annemie
Abstract: CO2 conversion by a gliding arc plasma is gaining increasing interest, but the underlying mechanisms for an energy-efficient process are still far from understood. Indeed, the chemical complexity of the non-equilibrium plasma poses a challenge for plasma modeling due to the huge computational load. In this paper, a one-dimensional (1D) gliding arc model is developed in a cylindrical frame, with a detailed non-equilibrium CO2 plasma chemistry set, including the CO2 vibrational kinetics up to the dissociation limit. The model solves a set of time-dependent continuity equations based on the chemical reactions, as well as the electron energy balance equation, and it assumes quasi-neutrality in the plasma. The loss of plasma species and heat due to convection by the transverse gas flow is accounted for by using a characteristic frequency of convective cooling, which depends on the gliding arc radius, the relative velocity of the gas flow with respect to the arc and on the arc elongation rate. The calculated values for plasma density and plasma temperature within this work are comparable with experimental data on gliding arc plasma reactors in the literature. Our calculation results indicate that excitation to the vibrational levels promotes efficient dissociation in the gliding arc, and this is consistent with experimental investigations of the gliding arc based CO2 conversion in the literature. Additionally, the dissociation of CO2 through collisions with O atoms has the largest contribution to CO2 splitting under the conditions studied. In addition to the above results, we also demonstrate that lumping the CO2 vibrational states can bring a significant reduction of the computational load. The latter opens up the way for 2D or 3D models with an accurate description of the CO2 vibrational kinetics.